PENERAPAN METODE PEMBELAJARAN CARD SHORT DALAM MENINGKATKAN MOTIVASI BELAJAR SISWA KELAS IV SD NEGERI 0607 PAGARAN BATU - Era Mutiah; Harahap, Nurhalimah; Egi Alex Saputra Daulay (Yayasan Perguruan Kampus, 2025)
The objectives in this study were (1) To determine the application of the card shot method in increasing student learning motivation in class IV of SD Negeri 0607 Pagaran Batu. This research uses a type of field research, the design used is PTK, namely class action research. In this case the researcher can act as an active participant in the main activity, agent. There are two sources of data in this study, namely primary data sources and secondary data sources. Primary data sources are data directly taken from the object of research, namely students and class IV teachers. This primary data source comes from field data obtained from observations and interviews. Secondary data sources are data taken in the form of documents, such as books, and other literature related to increasing student learning motivation. The design of this research cycle is three cycles, namely Pre Cycle, Cycle I and Cycle II. The results of research on student learning motivation show that in the pre-cycle student scores are still below the KKM, namely the average student score of 58.8. Students who completed as many as 7 students with a percentage of 43.8% and students who did not complete as many as 9 students with a percentage of 56.3%. Then student learning motivation in cycle I student scores have begun to increase with an average student score of 64.4. Students who completed as many as 8 students with a percentage of 50% and students who did not complete as many as 8 students with a percentage of 50%. Then student learning motivation in cycle II, student scores have increased with an average student score of 81.9. Students who completed as many as 14 students with a percentage of 87.5% and students who did not complete as many as 2 students with a percentage of 12.5%. The results showed that in increasing student learning motivation in Class IV SD Negeri Pagaran Batu has implemented a good learning process.